ON THE PROBLEM OF WATER TEMPERATURE INFLUENCE ON SEASONAL GROWTH OF JUVENILE COHO SALMON ONCORHYNCHUS KISUTCH IN THE LOWER REACHES OF THE BOLSHAYA RIVER IN 2007–2018 - V. F. Bugaev; N. A. Rastyagaeva; T. N. Travina (Известия ТИНРО)
The water temperature difference between relatively cold and warm years is not significant for somatic growth and number of sclerites in the external zone of scale out of the annual ring («plus zone») for yearlings of coho salmon in the lower stream of the Bolshaya River (West Kamchatka). The temperature effect is ambiguous and depends on month. In 20 days since May 15, number of the sclerites formed in this zone is definitely higher in warm years (0.77 sclerites, on average) than in cold years (0.51 sclerites), but in 120 days the difference almost disappears: 10.39 sclerites in warm years and 10.13 sclerites in cold years. So, each scleritis forms in approximately 10.4 days during June-August, no matter either warm or cold year it is. In September, the number of sclerites in the «plus zone» could be even smaller in some warm years than in some cold years. The temperature effect absence can be explained by low temperature in the river during the whole period from May to October (6.44 о C in May, 8.80 о C in June, 11.83 о C in July, 12.25 о C in August, 10.10 о C in September, and 6.33 о C in October, on average), that is close to the lowest limit of the optimal temperature range for coho juveniles (11.5–16.8 о C). Difference of the yearlings body length is also insignificant: in the period of 20–90 days from May 15 of 2007–2018, their mean body length increased in 2–5 mm more in the years with temperature above the norm in July than in the years with temperature below the norm, but within the period from middle May to late August the increments values coincide frequently for both types of years. All differences in the body length and number of sclerites between the coho yearlings in warm and cold years do not exceed the level of statistical errors. That’s why merging of all materials on juvenile coho salmon in the Bolshaya River is recommended, without their separation to cohorts of warm and cold years.